2015
DOI: 10.1037/a0038442
|View full text |Cite
|
Sign up to set email alerts
|

Impact of violence research on participants over time: Helpful, harmful, or neither?

Abstract: Objective To investigate the impact of answering survey questions about experiences of stressful, stigmatizing, potentially traumatic and sexually violating events on well being, defined as reactions to research, anxiety, and positive and negative affect over two weeks. Method With an ethnically diverse sample of 559 higher education students, we employed a mixed experimental design (with between and within-subjects components) to evaluate changes in positive and negative affect, anxiety, traumatic stress sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…We limited our analyses in this report to graduate students. Although research on the sexual victimization of undergraduate women is currently burgeoning (e.g., Carey, Durney, Shepardson, & Carey, 2015;Cook, Swartout, Goodnight, Hipp, & Bellis, 2015;Orchowski & Gidycz, 2015;Warren, Swan, & Allen, 2015;Wigderson & Katz, 2015), research on the victimization of graduate students, male and female, is absent from recent studies. While undergraduates experience sexual harassment from both professors and other students, graduate students are in a potentially risky position for three reasons.…”
Section: The Current Studymentioning
confidence: 99%
“…We limited our analyses in this report to graduate students. Although research on the sexual victimization of undergraduate women is currently burgeoning (e.g., Carey, Durney, Shepardson, & Carey, 2015;Cook, Swartout, Goodnight, Hipp, & Bellis, 2015;Orchowski & Gidycz, 2015;Warren, Swan, & Allen, 2015;Wigderson & Katz, 2015), research on the victimization of graduate students, male and female, is absent from recent studies. While undergraduates experience sexual harassment from both professors and other students, graduate students are in a potentially risky position for three reasons.…”
Section: The Current Studymentioning
confidence: 99%
“…al., 2014), but can be mediated by severity of symptoms such as depression, anxiety, and PTSD (Massey & Widom, 2013). A more recent study showed that participants who were asked about sexual trauma had a slightly lower positive affect after two weeks compared to those who were only asked about stressful, but not traumatic, life events (Cook, Swartout, Goodnight, Hipp, & Bellis, 2015). Studies also find PTSD to be a unique predictor of negative reactions to participation (Edwards’s et.…”
Section: Study Participation Effectsmentioning
confidence: 99%
“…This concern is also reflected in a number of recently published articles in the popular media positing that college students are vulnerable and should be protected from controversial or evocative content (Lukianoff & Haidt, 2015; Freeman, Herrera, Hurley, King, Luciano, et al, 2014). Researchers studying sensitive topics have noted that they encounter barriers to obtaining IRB approval for trauma or sex related research (Cook, Swartout, Goodnight, Hipp, & Bellis, 2015; Jaffe, DiLillo, Hoffman, Haikalis, & Dykstra, 2015; Yeater, Miller, Rinehart, & Nason, 2012). However, a growing body of research now shows that participants are not emotionally distressed by such research – in fact, they find it enjoyable, interesting, and valuable, contrary to IRB assumptions (Carter-Visscher, Naugle, Bell, & Suvak, 2007; Cromer, Freyd, Binder, DePrince, & Becker-Blease, 2006; Edwards, Sylaska, & Gidycz, 2014; Jaffe et al, 2015; Jorm, Kelly, & Morgan, 2007; Labott, Johnson, Fendrich, & Feeny, 2013; Widom & Czaja, 2005; Yeater, et al, 2012).…”
mentioning
confidence: 99%